2019
DOI: 10.1590/1678-4162-10661
|View full text |Cite
|
Sign up to set email alerts
|

Variações fisiológicas, influência da idade e sexo no perfil bioquímico sanguíneo de aves da linhagem pesada de frango de corte na fase de recria

Abstract: RESUMO Este estudo teve o objetivo de comparar o perfil bioquímico sérico de machos e fêmeas da linhagem pesada de frango de corte, nas idades de quatro, 12 e 20 semanas, em uma unidade de produção industrial, no município de Uberlândia-MG. Após a pesagem das aves, foram coletadas amostras de sangue de 15 aves de cada sexo de cada faixa etária. Os soros obtidos foram avaliados em analisador automático para os seguintes parâmetros bioquímicos: proteína total, albumina, globulinas, ácido úrico, colesterol, trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Aspartate aminotransferase is responsible for the synthesis of this metabolite. The enzyme is found at high concentrations in various organs and tissues, particularly in the heart, liver, skeletal muscle, kidney, and brain ( Kaneko et al, 2008 ; Rezende et al, 2019 ). According to MacRae et al (2006) , serum activity of this enzyme serves as an enzymatic marker of muscle changes, including both muscle damage and increases in muscle mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspartate aminotransferase is responsible for the synthesis of this metabolite. The enzyme is found at high concentrations in various organs and tissues, particularly in the heart, liver, skeletal muscle, kidney, and brain ( Kaneko et al, 2008 ; Rezende et al, 2019 ). According to MacRae et al (2006) , serum activity of this enzyme serves as an enzymatic marker of muscle changes, including both muscle damage and increases in muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…According to MacRae et al (2006) , serum activity of this enzyme serves as an enzymatic marker of muscle changes, including both muscle damage and increases in muscle mass. A study on broiler chickens demonstrated an increase in the serum levels of this enzyme during the final growth phase ( Rezende et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress, endogenous corticosterone, and endogenous steroid hormones can cause elevations in cholesterol levels in Darwin’s rhea [ 18 ]. A survey on the biochemical profile of broiler birds carried out a comparison of age groups and sex of these species and reported lower values of uric acid and cholesterol in males [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…At 21 days of age, a single fasting bird from each repetition (30 units in total) was taken for total blood glucose quantification (Rezende et al, 2019), with the use of a portable digital glucometer (G-Tech Lite ® , South Korea). Then, the birds were slaughtered and their organs (liver, pancreas, gizzard, and intestines) removed and weighed immediately.…”
Section: Methodsmentioning
confidence: 99%